This article reported risk preferences and the consequences on tobacco farming in Pamekasan. Frontier production function model with heteroskedastic error structure estimated by maximume likelihood estimation developed by Kumbhakar was adopted to analyze the goals. This model can capture the effect of risk preference on input allocation, inefficiency and productivity. Four hundred fifty samples were drawn by cluster sampling method. The results show that risk preferences were not depended - Elys Fauziyah; Sri Hartoyo; Nunung Kusnadi; Sri Utami Kuntjoro (Forum Pasca Sarjana, 2010)
This article reported risk preferences and the consequences on tobacco farming in Pamekasan. Frontier production function model with heteroskedastic error structure estimated by maximume likelihood estimation developed by Kumbhakar was adopted to analyze the goals. This model can capture the effect of risk preference on input allocation, inefficiency and productivity. Four hundred fifty samples were drawn by cluster sampling method. The results show that risk preferences were not depended on agroecosystem and farming system, but they were determined by farm size. Most of the farmers prefered to avoid production risk. The consequences were input allocation under optimum condition, technical and allocative efficiencies at a low level, and depleted productivity. Key words: productivity, production risk, risk preference, inefficiency